Pengaruh Pengaruh Profitabilitas, Leverage, Pertumbuhan Penjualan, dan Kepemilikan Institusional Terhadap Penghindaran Pajak - Tri Mahmudi; Kartika Hendra Titisari; Sari Kurniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Tax avoidance is a legal action taken against taxpayers by taking advantage of certain tax loopholes to avoid paying the tax burden and enabling the company to obtain the expected profit. Testing and research analysis of the effect of profitability, leverage, sales growth, and institutional ownership on tax evasion is the research objective. This research uses a purposive sampling method, the number of samples is 120 samples or 40 companies that go public in the consumer non-cyclical sector which are listed on the Indonesia Stock Exchange in 2019-2021. The data used secondary data in the form of annual financial reports with an analytical model, namely multiple linear regression analysis with SPPS Statistics version 25 software. The results show that profitability, leverage, and sales growth effect on tax avoidance. While institutional ownership have no effect on tax avoidance.. Keywords: profitability, leverage, sales growth, institutional ownership.